Comparing Risk Changes of Needlestick Injuries between Countries Adopted and Not Adopted the Needlestick Safety and Prevention Act: A Meta-Analysis - Fatimah Saleh Al Herz; Fatimah AL-Dhamen; Zahra Ibrahim Alzawad; Salma Abdulaziz Alzayer; Zainab Ali ALObaidi; Narjes Jawad Aljaroodi; Zainab Redha Alshaban; Bassimah Mohammed Reda Alboori; Zahra Al Harz; Zahra Abdulhameed AlZurigi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Needlestick injuries (NSIs) are a prevalent occupational hazard among healthcare workers (HCWs). They elevate the possibility of contracting bloodborne infections, including hepatitis C virus, hepatitis B virus, and human immunodeficiency virus. The prevention of needlestick injuries may be achieved through the utilization of needles with safety-engineered devices. Aim: To compare the risk changes of needlestick injuries between countries adopted and not adopted the needlestick safety and prevention act. Materials and methods: This meta-analysis has been carried out on 11 studies according to the guidelines by the Cochrane Collaboration reporting followed the PRISMA statement (Preferred Reporting Items for Systematic Reviews and Meta-analyses). Main findings: Two studies reported (NSI incidence among nurses) and all can be used. A significant heterogeneity was detected. Therefore, a random-effect model has been utilized for analysis (I²-value = 80%, P-value=0.03). The combined mean difference and 95 percent CIs was 1.13 (1.07 to 1.20). The combined result demonstrates highly statistically significant difference between groups regarding (NSI incidence among nurses) (Z = 4.15, P ≤0.001). One study reported (NSI frequency among nurses in unlegislated countries) and all can be used. The result demonstrates highly statistically significant difference between groups regarding (NSI frequency among nurses in unlegislated countries) (Z-value = 3.30, P-value ≤0.001). Conclusion: The frequency of NSIs among healthcare workers reduced significantly in countries with SEMD legislation in comparison to those without. Improved regulations may result from further investigation to ascertain if such reductions vary among occupational subgroups.